Karst terrain in the western upper Galilee, Israel: Speleogenesis, hydrogeology and human preference of Manot Cave. Issue 160 (November 2021) - Frumkin, Amos; Barzilai, Omry; Hershkovitz, Israel; Ullman, Micka; Marder, Ofer
Abstract: A karst survey of the western upper Galilee in Israel shows that karst has been a dominant geomorphic factor throughout the Cenozoic. We discuss the geomorphic character of Manot Cave on the background of other karst features of the region, in order to decipher the preferences of the humans who favored this cave over others. Tens of caves distributed over the study area demonstrate that phreatic and hypogene isolated voids and conduit segments are more abundant than vadose shafts, sinking stream caves and spring caves, although all these types are present. Most caves belong to old stages of landform development, prior to Plio-Pleistocene uplift and stream entrenchment. Manot Cave is a relict chamber cave, which corresponds to a plaeo-water table and the erosion plain above it. Subaerial denudation and slope processes have opened the cave to the surface during the mid-late Pleistocene. Manot Cave is compared with other caves in the region, demonstrating its unique character. It may have been selected due to the small entrance facing to the SW, and the large inner chamber which could be used for non-domestic purposes. This suggests a possible role of a unique behavioral and cultural suite of characters which influenced hominin preferences. The cave was used by hominins and animals until being closed again by colluvium and possibly collapse, ∼30 ka. Clastic, chemical, archaeozoological and anthropogenic accumulations reflect the various stages of cave development and gradual sealing of the entrance.